(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The primary aim of our study was to delve into the neuroprotective potential of an ethanolic extract sourced from Alternanthera sessilis, particularly in alleviating behavioural impairments induced by reserpine in rat models simulating stroke and seizures. Our investigation involved categorizing rats into five distinct groups, each consisting of six individuals, with separate sets allocated for different experimental interventions. Seizures and stroke-like symptoms were induced by administering reserpine, after which the rats underwent treatment with varying doses of Alternanthera sessilis ethanolic extract. We conducted a comprehensive assessment of various behavioural parameters, including antiepileptic activity, motor function, overall well-being, rota rod performance, closed field activity, and grip strength. Significantly, our results uncovered substantial improvements in antiepileptic activity, motor function, and overall health of the intervention group, which received the extract, to the control group after the administration period. Additionally, enhancements were noted in rota rod performance, closed field activity, and grip strength, indicative of a marked enhancement in neuroprotective effects. These encouraging findings highlight the potential therapeutic efficacy of Alternanthera sessilis extract in managing stroke and seizure disorders. Nevertheless, further extensive investigations are imperative to unravel the precise mechanisms underlying these observed enhancements. Furthermore, future research endeavors should focus on delineating the specific therapeutic applications of Alternanthera sessilis extract, thus facilitating its potential integration into clinical practice for the management of stroke and seizure-related conditions. This would pave the way for a more comprehensive understanding of its therapeutic benefits and broaden its scope for clinical utility.